(untitled) (UNED Research Journal, 2017)
In distance education, tutorials system are important to guide learning process, through diagnostic, formative or summative evaluation. However, in some cases, tutorials are overrated, and generate isolation and disorientation. To improve tutoring, we did two workshops with tutors in a Costa Rican distance university, and found that traditional and distance tutoring need to be different. Some tutors do not have enough training in orientation and suffer from absenteeism and lack of familiarity with some topics. On the other hand, they tend to use varied motivation strategies. We also recommend the use of other technologies, such as virtual laboratories and Second LifeTM , and strengthening administrative factors.